Microcracks pattern and the degree of weathering in granite - Omar, Husaini; Mohd Pauzi, Nur Irfah; Abu-Shariah, Mohammed; Md Yusoff, Zainuddin; Maail, Shukri (Electronic Journal of Geotechnical Engineering, 2009)
Fractures in granite rocks can develop in many characters in terms of the density of fractures, complex composite microcrack systems are caused by different geologic processes under varying condition. The objective of the research is to study the relationship between microcrack pattern and the weathering degree of granite at Pos Selim area, Malaysia. The fractures on the sheared surface are measured based on the Scanning Electron Microscope (SEM) image. The microscopic aspects of fracture such as trans-granular crack, open cracks are measured using SEM before and after shearing test which is called pre-shear and postshear respectively. Each of the fractured surfaces are measured and analyzed to come out with the fractured pattern of the weathered granite in different normal load and shear load. From the studies, the microcrack propagation patterns can be categorized into two type which are type A and type B. Type A is microcrack propagation pattern for granite grade II and type B is microcrack propagation pattern for granite grade III. Type A microcrack propagation pattern does not lead to failure and consists of minor crack surface. Type B material show microcrack pattern that propagates from the left side of the sample leading towards the right side of the sample which caused failure of the material. The relationship between the microcrack pattern and the shear strength and normal stress would result in increase of microcrack area, and intergranular cracks appears depend upon the mineralogy of the granite.parameters proves that an increase in shear stress and normal stress would result in increase of microcrack area, and intergranular cracks appears depend upon the mineralogy of the granite.